Transición del plan vallejo tradicional al plan vallejo express (2022)
Colombia is an open and free market country, a territory that is known for several of its export products, especially traditional export items. Although the nation is known to other countries, it must compete in the international market. Colombia must bet on international trade with its quality and its prices. Price is one of the main components for consumers to make purchase decisions and to be competitive, prices must be within the market benchmarks or below them.